Financial Development's Role in the 2030 Sustainable Development Agenda: Asian Countries - Suci Rismawati; Purbayu Budi Santosa (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The purpose of achieving sustainable development goals (SDGs) requires the mobilisation of finance and its alignment with sustainability principles. This study intends to examine the influence of financial development on the attainment of Sustainable Development Goals (SDGs) in an economy. Approach - The authors conduct an analysis of a sample comprising 35 Asian countries, focusing on their SDG (Sustainable Development Goals). Patterns and indicative indicators of the Sustainable Development Goals (SDGs). A probit model is used to analyse the effect of Financial development impacting the trajectory of the Sustainable Development Goals. Then, a pairwise Granger causality test is used for Examining the relationship between the Sustainable Development Goals and financial development The results suggest that there is a favourable relationship between financial development and the advancement towards the Sustainable Development Goals. The test for causation There is a reciprocal relationship between financial development and industry, infrastructure, and innovation. Enhancing financial growth and promoting sustainable cities and communities, as well as fostering financial development and taking action on climate change, There is a one-way relationship where gender equality influences financial progress. Research limitations/ramifications - The findings also have implications for the government of a nation as the privately-owned enterprises.